Numerical methods for nonlinear elliptic differential equations : a synopsis - q (Oxford : Oxford University Press, 2010)
The author proves in a systematic and unifying way stability, convergence and computing results for the different numerical methods for nonlinear elliptic problems. The proofs use linearization, compact perturbation of the coercive principal parts, or monotone operator techniques, and approximation theory.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Differential equations, Elliptic -- Numerical solutions; Differential equations, Nonlinear -- Numerical solutions